FEATURES OF APPOINTMENT AND CONDUCT OF SPEECH LINGUISTIC EXPERTISE (SEMANTIC- TEXTUAL AND AUTHORIAL EXPERTISE): JUDICIAL PRACTICE - Tatiana А. Todoroshko; Аlona V. Bila (Alfred Nobel University Journal of Law)
The article is devoted to the study of the peculiarities of linguistic expertise in the judicial process. The scientific work characterizes the concept of linguistic expertise, highlights the types of linguistic expertise, analyzes the features and differences of semantic-textual and author expertise, identifies the objects of expertise, describes the range of questions posed for linguistic expertise. It has been established that the linguistic expertise of speech plays an important role during the investigation of criminal proceedings and the consideration of court cases, and its conclusions serve as a basis for protecting the interests of the state and its citizens. It is noted that the forensic semantic- textual expertise of the text within the framework of court proceedings is carried out in accordance with the norms defined by the Instructions on the appointment and conduct of forensic expertises and expert studies and Scientific and methodological recommendations on the preparation and appointment of forensic expertises and expert studies, approved by the order of the Ministry of Justice of Ukraine. In turn, the legal nature of linguistic expertise is due to the availability of special knowledge in the field of science, which allows establishing or refuting facts that are of great importance in the consideration of a court case and the resolution of a dispute. It has been analyzed that the direct theoretical study of linguistic expertise does not allow to form a holistic and objective idea about its nature, as well as its importance in the process of law enforcement and establishing the truth in the case. In particular, the procedural procedure for the appointment of a linguistic expertise was clarified, and the judicial practice regarding the consideration of cases in which a linguistic expertise was appointed was analyzed.